Penyuluhan Hukum Tentang Peran Majelis Krama Desa Dalam Mencegah Perkawinan Anak Di Kabupaten Lombok Utara - RR. Cahyowati; Rodliyah Rodliyah; Risnain Risnain (Pascasarjana Universitas Mataram, 2020)
The number of child marriage in Indonesia is the second highest after Cambodia for the ASEAN region. Child marriage needs serious attention because it results in the loss of girls' rights, such as education, play, protection, security, and others, including the impact on health. The problem faced in NTB is the high number of child marriages, which are in the 10th National ranking. The purpose of this counseling is to provide knowledge to the community in Bentek Village regarding the Role of the Krama Desa Council in preventing child marriage in North Lombok Regency. As a result, the Krama Desa Assembly in Bentek Village consists of 9 administrators with an operational cost in 2020 of Rp. 20,000,000, -, cases filed by the community in Bentek Village are resolved in